Determinants of Labor Productivity in Emerging Markets: Evidence from Pre- and Post-Financial Crisis Mexico - Young-Hee Kang; Kyunga Na (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2018)
Although the global financial crisis of 2008 had tremendous effects on global businesses, its impact on firm performance in emerging markets is unknown. To develop this knowledge, this study explores the factors that influenced labor productivity in emerging markets before and after the crisis. Using a sample of 2,061 Mexican firms that were collected by the World Bank in 2006 and 2010, this study investigates the relationships of bribery, informality, and corporate governance to labor productivity. The results show that, before the crisis, informality and foreign ownership were positively associated with labor productivity. On the other hand, after the crisis, bribery and informality are negatively related to labor productivity, while foreign ownership and external auditing make positive impacts on labor productivity. The findings imply that businesses need to improve the quality of their corporate governance and decrease bribery. Governments of emerging markets need to reduce the levels of informality.